The words you should to sound smart : 1,200 essential words every sophisticated person should be able to use - Bly, Robert W. (Adams Media, 2009)
A tongue-in-cheek guide to words that a smart, well-educated, pretentious person should be able to drop into cocktail conversation. It helps the reader to toss off words such as 'Disestablishmentarianism', 'descant', and 'autodidactic', proving, if not the value of a good education, at least the appearance of a good education